2009
DOI: 10.1088/0029-5515/49/3/032002
|View full text |Cite
|
Sign up to set email alerts
|

Prompt ignition of a unipolar arc on helium irradiated tungsten

Abstract: A fibreform nanostructured layer is formed on a tungsten surface by helium plasma bombardment. The helium fluence was of the order of 1026 m−2, and the surface temperature and incident ion energy during helium irradiation were, respectively, 1900 K and 75 eV. By irradiating a laser pulse to the surface in the plasma, a unipolar arc, which many people have tried to verify in well-defined experiments, is promptly initiated and continued for a much longer time than the laser pulse width. The laser pulse width (∼0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
103
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 123 publications
(108 citation statements)
references
References 26 publications
(32 reference statements)
4
103
0
1
Order By: Relevance
“…The main difference is in the comparison of the surface morphologies for the maximum surface temperatures in the transient experiments (Alcator C-Mod and Pilot-PSI) and the equivalent steady-state surface temperatures from other experiments. Through experiments with steadystate surface temperatures it has been well documented that W nano-tendrils begin to form at ~1000 K, and as surface temperature increases, the nano-tendrils' diameter increases until at ~2000 K the individual nano-tendrils become indistinct and the surface is populated with I-10 9 large pores [10]. For the transient surface temperature exposures on Pilot-PSI, a similar transition from fine to coarse nano-tendrils is seen as the maximum surface temperature rises, finally transitioning to large surface pores at the highest surface temperatures, but the thresholds are different.…”
Section: Comparison Of Alcator C-mod Results To Pisces and Pilot-psimentioning
confidence: 99%
See 1 more Smart Citation
“…The main difference is in the comparison of the surface morphologies for the maximum surface temperatures in the transient experiments (Alcator C-Mod and Pilot-PSI) and the equivalent steady-state surface temperatures from other experiments. Through experiments with steadystate surface temperatures it has been well documented that W nano-tendrils begin to form at ~1000 K, and as surface temperature increases, the nano-tendrils' diameter increases until at ~2000 K the individual nano-tendrils become indistinct and the surface is populated with I-10 9 large pores [10]. For the transient surface temperature exposures on Pilot-PSI, a similar transition from fine to coarse nano-tendrils is seen as the maximum surface temperature rises, finally transitioning to large surface pores at the highest surface temperatures, but the thresholds are different.…”
Section: Comparison Of Alcator C-mod Results To Pisces and Pilot-psimentioning
confidence: 99%
“…However, we do not have measurements of the heat flux received by the W probe during these disruptions. There is also no evidence of the uni-polar arcing that was seen on nano-tendril surfaces exposed in the LHD stellerator [9] and in NAGDIS-II [10].…”
Section: Alcator C-mod Exposuresmentioning
confidence: 87%
“…3 Recent studies have shown that transient heat loads on the divertor, such as Edge Localized Modes (ELMs), might trigger unipolar arcing, and that fuzz significantly increases its ignition. 4 The existence of the unipolar arc has been confirmed phenomenologically by erosion craters found in numerous fusion devices: JT-60U, LHD, 5 DIII-D, 6 and ASDEX Upgrade. 7,8 Moreover, since the arcing may take place in fusion experiments, special model experiments have been conducted for a systematic study in which arcing is initiated by plasmas generated by a high-frequency discharge, 9,10 a plasma gun, 11,12 and a laser beam.…”
Section: à3mentioning
confidence: 94%
“…7,8 Moreover, since the arcing may take place in fusion experiments, special model experiments have been conducted for a systematic study in which arcing is initiated by plasmas generated by a high-frequency discharge, 9,10 a plasma gun, 11,12 and a laser beam. 4,13,14 What is missing is an investigation into the properties of (unipolar) arc-induced plasma, which requires proper diagnostics. This research uses the transient heat load of a laserpulse to trigger unipolar arcing on fuzzy tungsten and has the aim to spectroscopically characterize the arc-induced plasma.…”
Section: à3mentioning
confidence: 99%
“…The surface characteristics of thus formed tungsten plate would change compared with the flat non-damaged surface, for example, the radiation emissivity [3], the sputtering yield [4], the heat conduction [5], the discharge property [6] and so on. In this report the secondary electron emission (SEE) property will be discussed in relation to the floating potential which is important with respect to the impurity releases through physical sputtering and plasma heat flux.…”
Section: Deepening Of Floating Potential For Tungsten Target Plate Onmentioning
confidence: 99%